LEARNING STRATEGY OF BRAIN RHYTHM METHOD ON AL-QURAN MEMORIZATION OF MTA SURAKARTA HIGH SCHOOL STUDENTS - Khotimah, Isnaini Nur; Azani, Mohammad Zakki (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
The Brain Rhythm Method is a method of memorizing the Al-Quran that uses tonal rhythm and makhaj rhythm techniques in the memorization process by paying attention to the correct legal rules of recitation. This research aims to test the effectiveness of applying the Brain Rhythm Method in improving the quality of Al-Quran memorization in MTA Surakarta High School students. Some intensive tahfidz students experienced a decrease in enthusiasm for memorizing the Al-Quran. An interesting method was applied, namely the Brain Rhythm Method, which can help improve students' memorization of the Al-Quran. Researchers use a qualitative approach, with descriptive analysis research methods. In this study, researchers interviewed 4 musyrifah tahfidz alumni of Kuntum Indonesia, who taught the Brain Rhythm Method at SMA MTA Surakarta. The research object was 100 intensive tahfidz female students. The results of this research can be concluded that the implementation of the Brain Rhythm Method went smoothly and was proven to be effective in improving understanding and quality in memorizing the Al-Quran. This method can also increase students' enthusiasm for memorizing. And the evaluation results obtained were very satisfying, many students achieved targets and exceeded memorized targets. Of course, all of this is the result of collaboration between all parties involved in implementing the Brain Rhythm Method.